Modern methods of teaching physics in universities - Spolnik , O.; Gaidus , A.; Kaliberda , L. (New Collegium, 2021)
The article analyzes the difficulties faced by physics teachers in higher educational institutions. The modern information-communication and educational technologies are considered, which make it possible to improve the quality of teaching physics and the assimilation of the discipline by students. The role of distance learning (DL) is emphasized in the context of a limited number of hours devoted to physics. The article examines the global trends in the development of distance learning, analyzes the role of this form of education in the modern educational process and the factors affecting the development of DL. Attention is drawn to the difficulties of implementing a virtual laboratory practice, without which it is impossible to implement full-fledged teaching of physics remotely. The use of virtual works allows observing the main principle of didactics – visualization. Visibility provides optimal assimilation of the material by increasing the emotional perception of the material and the use of all types of thinking in students. The need for high realism of experiments in virtual laboratories, accuracy of reproduction of the physical laws and the essence of experiments and phenomena. This allows students to develop skills in experimental work. The implementation of high variability in the conduct of experiments and initial data allows you to increase the efficiency of using a laboratory practice in computer classes. The paper discusses the most available software tools for creating. In the article analyzes modern teaching technologies, the application of which radically changes the approach to the educational process. In the article discusses such popular and effective brands of educational technologies as adaptive web resources Cerego, Grockit, Smart Sparrow, as well as adaptive technologies based on distance learning systems – Blackboard, Desire2Learn, ILIAS, Lotus Learning Space, Moodle allowing to analyze the level of learning student teaching material. The high potential possessed by mobile technologies in the distance-learning environment is noted.